A passion for facts : social surveys and the construction of the Chinese nation-state, 1900-1949 - Lam, Tong, 1967- (Asia Pacific modern, 2011)
"In this path-breaking book, Tong Lam examines the emergence of the "culture of fact" in modern China, showing how elites and intellectuals sought to transform the dynastic empire into a nation-state, thereby ensuring its survival. Lam argues that an epistemological break away from traditional modes of understanding the observable world began around the turn of the twentieth century. Tracing the Neo-Confucian school of evidentiary research and the modern departure from it, Lam shows how, through the rise of the social survey, "the fact" became a basic conceptual medium and source of truth. In focusing on China's social survey movement, A Passion for Facts analyzes how information generated by a range of research practices--census, sociological investigation, and ethnography--was mobilized by competing political factions to imagine, manage, and remake the nation"--Provided by publisher